The Correlation between Iron and Protein Intake in the Hemoglobin Levels of the Faculty of Medicine Students, Unram - Cholidah, Rifana; Amalia, Emmy; Danianto, Ario; Purnaning, Dyah; Ananda, Asti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
naemia is a global burden disease that mostly occurs in the reproductive age. About 31.2% of women of reproductive age (15-49 years) have anaemia. This condition may affect oxygen transport in the body and interfere with some bodily functions. Several factors may induce anaemia; iron deficiency is one of them. An amount of iron and protein intake may contribute to haemoglobin levels. This study aims to determine the correlation between iron and protein intake and haemoglobin levels among students in the Faculty of Medicine at the University of Mataram. This is an observational analytic study using cross-sectional methods that includes students aged 17-20 years old. Data is taken in May–June 2024 using a spectrophotometer for checking haemoglobin levels. Iron and protein intake were traced by a 24-hour food records questionnaire over 2 days. Results: There are 118 samples with 25.42% male and 74.58% female. Normal mean haemoglobin levels were detected in this study (12.59±0.82). The correlation tests, with the t-test for iron and protein intake, are not significant, with p-values of 0.246 and 0.254, respectively. Also, total protein and iron intake from this study, with an Anova F-test, is not significant, with a p-value of 0.408. The amount of consumption of iron and protein intake is not significant in the hemoglobin levels of Faculty of Medicine Students of the University.